VARIATION IN DISTRIBUTING AGRICULTURAL INCOME (A STUDY IN RURAL POVERTY) “DEVELOPING STATES FOR THE YEAR 2003” AS AN EXAMPLE - Alaa M. Abdullah (Mesopotamia Journal of Agriculture)
The importance of the research comes to show the effect of variation in income distribution upon the rates of agricultural product in selective developing countries for the years 2003 by applying a hypothesis which says that poverty may lead to more income variation and more rural poverty in developing countries .The research aims at studying this relationship and to have an answer for the following question :Can an agricultural growth be achieved with the existence of large variation in income distribution ?The statistical results by using the simple square method f two stages 2SLS appeared the positive and significant relationship for the variance of agricultural work to the total work X2 and inflation rate X4 in affecting Gini Coefficient .The increase in value X2 & X4 by 20.6 and 0.41 units respectively and this will produce effects with the same direction in increasing the variance level for distributing in come .The variance of agricultural work ratio to the number of population X3 has confirmed that it has negative and significant effect in Gini Coefficient throughout its index by 46.1 units .As for the increases taken place in Gini Coefficient it has produced small increases in the rate of annual agricultural product to the total domestic product .The value of index in Gini is estimated 0.10 units and shows that the growth of income distribution which represents Gini Coefficient participates actively in affecting rtes of agricultural product for a sample of studied countries .This will lead to an increase of rural poverty in a short term .